Plasma levels of beta-endorphin and serotonin in response to specific spinal based exercises - O. Sokunbi; A. Moore; P. Watt (AOSIS, 2008)
Exercises as the primary mode of treatment for low back disorders aim to achieve pain reduction, improvement in functional abilityand quality of life of for low back disorder sufferers. However the bio-chemical events associated with the use of these exercises in terms of theireffects on pain relieving neuropeptides have not been well established. Thisstudy was carried out to investigate the effects of spinal stabilisation, backextension and treadmill walking exercises on plasma levels of serotonin andbeta-endorphin.Twenty volunteers (10 males and 10 females) without low back pain participated in the study. They were randomly allocated either to one of theexercise groups, where participants carried out one of the spinal stabilisation, back extension and treadmill walkingexercises or the control (no exercise) group. The main outcome measures used in this study were plasma levels of serotonin and beta-endorphin measured with Enzyme linked immuno absorbent assay (ELISA) technique.The results of this study showed that spinal stabilisation and treadmill walking exercises produced significantincrease in plasma serotonin levels (P < 0.05) however there were no significant changes in the plasma levels of beta-endorphin in all the exercise groups (P > 0.05).It could be that biochemical effects associated with stabilisation and treadmill walking exercises therefore mayinvolve production of serotonin and its release into the plasma.